战后台湾闽南流行歌曲的兴起与演变：以行业歌曲为例 (The Emergence And Evolution Of Post-War Minnan Popular Songs In Taiwan: A Case Study Of Industry Songs) - Teh, Ke Li (2019)
This thesis will focus on the emergence and evolution on Minan popular songs after post-war in Taiwan. There are many creation types of Taiwanese Minnan Song, such as family love, romance, homesickness, industries, and etc. This case study will focus on Taiwanese Minnan Industry Songs. As Taiwan is a country originally with an agricultural society, it began to carry out an economic transformation plan after end of the post-war. The songs of each era reveal the social environment of different eras. Therefore, this thesis divides with several different periods to analyze these Industry songs. At the beginning of post-war period, Taiwanese Minnan Songs had a great and grand occasion before government proceed with Speak Mandarin movement. However, during the middle of post-war period, due to government’s suppression of Taiwanese Minnan language, the productivity of Taiwanese Minnan Songs began lesser in this period. Until the end of Chiang Kai Shek's era, the creation and productivity of Taiwanese Minnan Songs began to rise again. Therefore, this thesis analyzes the changes of Taiwanese Minnan pop music from the early folk songs to pop songs. The thoughts within female was changed since post-war era and hence this thesis also analyze the role of female in the workplace from different periods. There are several varies way of music transmitted to public.